Design Method of Differential Cascading for Dual-Stator Brushless Doubly-Fed Induction Wind Generator With Staggered Dual Cage Rotor - Zeng, Yu; Cheng, Ming; Yan, Xiaoming; Zhang, Changguo (Frontiers in Energy Research, 2021)
This article proposes a new differential-cascading-based dual-stator brushless doubly-fed induction machine with a staggered dual cage rotor. Conventional differential mode of the brushless doubly-fed machine with cage rotor suffers from the low number of rotor bars because of the low equivalent synchronous pole pairs of |p1-p2|, and thus, severe rotor flux leakage, low capacity of magnetic field conversion of the rotor and low efficiency. To overcome the obstacle of the excessive harmonics of the rotor, a design method based on the differential cascading is proposed which enables the cage rotor with a high number of conductor bars even in the case of low pole pairs of |p1-p2|, hence the greatly reduced rotor leakage inductance and enhanced performance of the machine. The rotating magneto-motive force theory is applied to derive the interconnection rule of the staggered dual cage rotor, and meanwhile, the corresponding examples are illustrated. The performance comparisons between the differential cascading and the sum cascading based on the proposed machine are carried out. The results show that the proposed machine based on the differential cascading obtains higher power densities comparing to the sum cascading at the region of sub-natural synchronous speed, while its drawback is the increment of the loss due to the high rotor frequency, gaining lower efficiencies at the region of super-natural synchronous speed.